Media Belajar Asah Hitung Matematika Berbasis Android - Dwi Dani Apriyani (Universitas Indraprasta PGRI Jakarta, 2022)
The concept of mathematical calculations is often used in everyday life. To enhance students' ability to count, it is necessary to practice counting. By doing a lot of soa; mathematical calculations students can get used to counting numbers. This numeracy lesson is also applied to the teaching and learning process in schools. The teaching and learning process in schools can be assisted by learning media so that they can achieve learning objectives. Android, which is easy to apply to various types of devices, is chosen to create an application for sharpening math calculations. This application can be downloaded and used anytime and anywhere. The ADDIE development model consists of analysis, design, development, implementation, and evaluation. The ADDIE model already contains components that are arranged systematically. The results of the validity test by the material expert are 81,95%. While the results of the media expert test with graphic aspects, button functions and efficiency are 81,36%.